Penyebar Islam di Pantai Utara Jawa: Mengungkap Peran Syaikh Quro Karawang - M. Syatibi Al-Haqiri (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2012)
This article deals with the roles of Syekh Quro as the most important Muslim preacher in Karawang and West Java. Syekh Quro was one of the Cheng Ho expedition in the beginning of the 15th century. Syekh Quro dropped by in Karawang and built his homebase to preach Islam there. His roles have not yet been well-written in the history of Islamization in the Archipelago. This is due to limited historical evidence. He successfully Islamized West Java and Pajajaran kingdom. His disciples were credited for disseminating Islam in West Java. He continued to spread Islam to Cirebon, Bekasi, and Jakarta. It is deemed important to give a great interest to conduct further research about him